Directory of Certified Deciduous Fruit and Nut Crop Nurseries in Florida - Peter C. Andersen; Robert C. Hochmuth; Sean R. McCoy; Lei Lani L. Davis (EDIS)
This 8-page fact sheet written by experts at North Florida REC Peter C. Andersen, Robert C. Hochmuth, Sean R. McCoy, and Lei Lani L. Davis, assists farmers in locating recommended cultivars of fruit and nut crops from Florida nurseries. The nurseries listed in Table 1 offer fruit and nut trees and are listed as certified nurseries with the Florida Department of Agriculture and Consumer Services. Table 2 lists fruit and nut cultivars that UF/IFAS Extension specialists currently recommend or suggest on a trial basis. Published by the UF Department of Horticultural Sciences, April 2013.